Urgensi Pendidikan Multikultural Berbasis Kearifan Lokal Bagi Siswa Sekolah Menengah Pertama - Nurwahid, Nurwahid (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Indonesia, as a multikultural country, is a nation's wealth that must preserve. Currently, it is increasingly sad because of the low level of multikultural education among students. There are many differences because of the cultural feel. One solution is to instill education that can do through multikultural based on local wisdom. The purpose of this paper is to provide an overview of the importance of multikulturalism and the learning of multikultural education based on local wisdom for elementary school (SD) students. The approach used is qualitative by conducting a literature review. The data analysis technique is descriptive qualitative. The result of this study is the importance of multikultural education for students. Elementary school teachers must design learning processes that integrate multikultural education based on local wisdom. This is part of a positive contribution to fostering students' nationalism and multikultural attitudes from an early age. Wisdom-based multikultural introduction aims to shape the character of the country's children who can accept, understand, and respect other people who are different in race, personality, social, ethnicity, customs, and religion. Multikultural education learning efforts in elementary schools are training and awareness for the younger generation to accept and appreciate all multikultural differences.